Activation Energy Measurement of Oxygen Ordering in a Nb-Ti Alloy by Anelastic Relaxation - Niemeyer, T.c. [UNESP]; Gimenez, J.m.a. [UNESP]; Almeida, L.h. [UNESP]; Grandini, C.r. [UNESP]; Florêncio, O. (ABM, ABC, ABPol, 2002)
Metals with bcc structure are able to dissolve large amounts of interstitial element atoms in the form of oxygen. These atoms diffuse through the lattice by jumping into octahedral sites with equivalent symmetry, causing strong alterations in the anelastic behavior. This paper reports on a study of Snoek relaxation in Nb-Ti alloys with oxygen in solid solution, based on internal friction as a function of temperature. The internal friction measurements were taken in a torsion pendulum operating at temperatures in the range of 350 to 650 K, with frequencies varying from 6 to 36 Hz. The results show relaxation spectra in which thermally activated relaxation peaks produced by the stress-induced ordering of oxygen atoms around niobium atoms of the metallic matrix were identified.
Keywords: anelasticity; internal friction; diffusion; niobium-titanium alloys